Solution
Asymptote:
Vertical Asymptote
- The vertical asymptotes of a rational function are determined by the denominator expression.
- The expression given is:
![f(x)=(6x)/(x-36)](https://img.qammunity.org/2023/formulas/mathematics/college/fzkrzp3o9wrzxzghav7u32ndj476ghb53s.png)
- The denominator of (x- 36) determines the asymptote line.
- The vertical asymptote defines where the rational function isundefined. Iin order for a rational function to be undefined, its denominator must be zero.
- Thus, we can say:
![\begin{gathered} x-36=0 \\ Add\text{ 36 to both sides} \\ \\ \therefore x=36 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r8mhhgh8rkm21vgdax74pgv9o3frdzrjls.png)
- Thus, the vertical asymptote is
![x=36](https://img.qammunity.org/2023/formulas/mathematics/high-school/3qy7yxikfklxgxbcsoelwrlq84h1xgwc2n.png)
Horizontal Asymptote:
- The horizontal asymptote exists in two cases:
1. When the highest degree of the numerator is less han the degree of the demnominator. In this case, the horizontal asymptote is y = 0
2. When the highest degee sof the numerator and tdenominator are the same. In this case, the horizontal asymptote is
![\begin{gathered} y=(N)/(D) \\ where, \\ N=\text{ Coefficient of the highest degree of the numerator} \\ D=\text{ Coefficient of the highest degree of the denominator} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dqbxv5db7sxmj3ukyugd52tbcaecmz32cb.png)
- For our question, we can see that the highest degrees of the numerator and denominator are the same. Thus, we have the Horizontal Asymptote to be:
![y=(6)/(1)=6](https://img.qammunity.org/2023/formulas/mathematics/college/zlqn2cjvio41msxv2lw2s6vdcavdw7atfq.png)
End behavior:
- The end behavior is examining the y-values of the function as x tendsto negative and positive infinity.
- Thus, we have that:
![\begin{gathered} f(x)=(6x)/(x-36) \\ \\ \text{ Divide top and bottom by }x \\ f(x)=(6x)/(x-36)*(x)/(x) \\ \\ f(x)=((6x)/(x))/((x-36)/(x))=(6)/(1-(36)/(x)) \\ \\ As\text{ }x\to-\infty \\ f(-\infty)=(6)/(1-(36)/(-\infty))=(6)/(1+(36)/(\infty))=(6)/(1+0)=6 \\ \\ \text{ Thus, we can say: }x\to-\infty,f(x)\to6 \\ \\ Also, \\ As\text{ }x\to\infty \\ f(\infty)=(6)/(1-(36)/(\infty))=(6)/(1-0)=6 \\ \\ \text{ Thus, we can also say: }x\to\infty,f(x)\to6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a94xgfwno55vqh6klue61wdvphkx3mdscd.png)
Final Answers
Asymptotes:
![\begin{gathered} \text{ Vertical:} \\ x=36 \\ \\ \text{ Horizontal:} \\ y=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wnmb9p9bskbwq8jplbdbjicnr0a0dnbhgb.png)
End behavior:
![\begin{gathered} As\text{ }x\to-\infty,f(x)\to6 \\ \\ As\text{ }x\to\infty,f(x)\to6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/22x4px4iggdxpnqtwo1p4m7wfenr8u226r.png)